Peculiarities of concentration dependences of thermal conductivity in (PbTe)₁₋ₓ (Bi₂Te₃)ₓ semiconductor solid solutions - Rogacheva, E. I.; Vodorez, O. S.; Nashchekina, O. N.; Dresselhaus, M. S. (Інститут термоелектрики НАН України, 2014)
For the semiconductor (PbTe)₁₋ₓ (Bi₂Te₃)ₓ solid solutions, the temperature (T = 250 – 670 K) and concentration (x = 0 – 0.07) dependences of the total λ and lattice λp thermal conductivities were obtained. It was established that the dependences λ(x), λp(x) and β(x) (where β is the exponent in the λp ~ T⁻ᵝ dependence) have a non-monotonic dependence on x in this range of x. While showing a general tendency to decrease with increasing x, the three variables λ, λp, and β exhibit maxima at x = 0.005, 0.015 and x = 0.03. The oscillatory character of these dependences is attributable to the changes in thermal transfer processes and the mechanisms of phonon scattering under transitions from the dilute to the concentrated and associated solid solutions, with the transitions due to spatial ordering processes. The effective cross-section σs for phonon scattering by impurity atoms was estimated on the basis of the experimental data and theoretical calculations in accordance with the Klemens theory. The mean σs value in the homogeneity region of PbTe (x = 0 – 0.05) found experimentally coincides with the theoretically calculated σs value. However, in the region of the dilute solid solutions (x < 0.005), the σs value considerably exceeds the mean σs value. Also long-term aging reduces λ by ~ 15%.
Keywords: solid solutions; thermal conductivity; isotherms; concentration anomalies; percolation; self-organization; critical phenomena